INTEGRASI MATERI PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA DI SMK MUHAMMADIYAH 2 BOJA - Miftahul Faoz; Syaiful Hadi (As-Sulthan Journal of Education, 2025)
Islamic religious education for the process of forming religious character for students. To be clear, Islamic religious education is the most important foundation that comes from actualizing character education. Education according to the important components, there is also the belief that there is an effective assumption for the formation of the character of the students, especially in realizing the religious character, not denying the components of the contents associated with Islamic religious education. Where the holders of interest roles in the lives of students with religious character models both in the world and in the hereafter. The growth and development of a good identity can begin with the religious spirit embedded in the students. This is where the meaning of character education is, therefore the Islamic religious education material taught in the school environment is one of the supporting values to base character education. Through Islamic religious education, students are taught aqidah when they are able to recognize elements of their religion based on the Qur'an or hadith in using guidelines to protect themselves in life. So, the main purpose of Islamic religious education is to shape the personality of students in the frame of reflection when they behave and do mindsets in life. In addition, the success value of various types of Islamic religious education learning in the school environment can be determined by the symptoms of accurate learning methods that are of interest to students.